A GAVeCeLT bundle for PICC-port insertion: The SIP-Port protocol - Brescia, Fabrizio; Annetta, Maria Giuseppina; Pinelli, Fulvio; Pittiruti, Mauro (The journal of vascular access, 2024)
In the last decade, a new type of brachial port has been introduced in clinical practice, the so-called "PICC-port." This is a brachial port, but inserted according to the methodologies and technologies currently adopted for the insertion of peripherally inserted central catheters (PICCs). Several studies have shown that PICC-port insertion is safe, not associated with any relevant immediate or early complication, and that the expected incidence of late complications is significantly lower if compared to "traditional" brachial ports (i.e. inserted without ultrasound guidance). Furthermore, PICC-ports yield excellent esthetic results and are associated with optimal patient compliance. This paper describes an insertion bundle-developed by GAVeCeLT, the Italian Group of Long Term Venous Access Devices, and nicknamed "SIP-Port" (Safe Insertion of PICC-Ports)-which consists of few evidence-based strategies aiming to further minimize all immediate, early, or late complications potentially associated with PICC-port insertion. Also, this insertion bundle has been developed for the purpose of defining more closely the differences between a traditional brachial port and a PICC-port. The SIP-Port bundle is currently adopted by all training courses on PICC-port insertion held by GAVeCeLT. It includes eight steps: (1) preprocedural ultrasound assessment utilizing the RaPeVA (Rapid Peripheral Venous Assessment) protocol; (2) appropriate skin antiseptic technique and maximal barrier precautions; (3) choice of appropriate vein, in terms of caliber and site; (4) clear identification of the median nerve and of the brachial artery during the venipuncture; (5) ultrasound-guided puncture and cannulation of the vein; (6) ultrasound-guided tip navigation; (7) intra-procedural assessment of tip location by intracavitary ECG or by trans-thoracic echocardiography; (8) appropriate creation and closure of the subcutaneous pocket.